Friendship of Jomi and Navoi as Symbol of Friendship of the Tajik and Uzbek People (Texas Journal of Philology, Culture and History, 2023)
In this article, on the example of friendship between Alisher Navoi and Abdurakhmoni Jomi, the issues of friendship between the Uzbek and Tajtk peoples are considered. To confirm the theoretical conclusions, numerous examples are given from the work of these two representatives of the fraternal peoples.